Parasite Biodiversity in Four Cyprinid Fishes from Beni-Haroun Dam (Mila City) North-East of Algeria - Berrouk, H; Allalgu, A; Kaouachi, N; Boualleg, C (My University, 2020)
Herein, the examination of 776 fishes related to 4 species of cyprinid fishes (Luciobarbus callensis, Cyprinus carpio, Carassuis carassuis and Abramis brama) and collected from Beni-Haroun dam promoted us to identify 99 infested individuals by 249 copepod parasites belonging to eight species, namely Ergasilus peregrinus, Ergasils briani, Ergasilus megaceros, Ergasilus sielboldi, Paraergasilus brevigiditus, Neoergasilus longispinosus, Neoergasilus japonicus and Lernea cyprinacea. The epidemiological study showed that the highest parasite indices were noticed in Cyprinus carpio (P% = 23.7, I =3.96 and A = 0.94) followed by Luciobarbus callensis (P% = 12. 84, I = 2.36 and A = 0.30), since the lowest values were observed in Abramis brama (P% = 5.63%, I = 1 and A = 0.05). Moreover, the parasite biodiversity based on the diversity indices that one time is related to the species host and at other times to season have shown that the determined parasite diversity considered weak in its group, as well as Luciobarbus callensis showed the very significant values of specific richness, followed by Carassuis carassuis and Cyprinus carpio, whereas Abramis brama hosts only two species. According to season, the very important values of parasite diversity was determined during summer followed by spring and fall, while the low values were noticed in winter. According to host fish criterion, the study showed two indicator species for Carassuis carassuis and three for Cyprinus carpio, in addition to three indicator species found during spring and three others during summer